Integrated risk governance in the Yungui Plateau, China: The 2008 ice-snow storm disaster - Qian Ye; Ming Wang; Jiarui Han (Revue de Géographie Alpine)
Yungui Plateau in Southwestern China is regarded as one of the major bio- and cultural diversity centers in the world because it contains a remarkable variety of ecological niches and ethnic groups. Due to its unique mountain geographic landscape and domination by a monsoon climate, it has high vulnerabilities and is frequently hit by various climatic and geological hazards such as droughts, floods, earthquakes, and landslides. In the past two decades, while the region has enjoyed rapid social and economic development, vegetation degradation, water pollution and soil loss, as well as other environmental problems, have become major concerns in the region. In January 2008, nearly half of China was hit by an unprecedented series of hazards of low temperature, persistent rain, snow, and a series of ice storms with South China suffering the most. In this paper, with a comprehensive overview of the causes and consequences of the disaster, a disaster chain in Yungui Plateau is identified and environmental, social, economic and political factors are analyzed under a framework of integrated risk governance.